2012
DOI: 10.1080/09540121.2012.687808
|View full text |Cite
|
Sign up to set email alerts
|

Social environment and HIV risk among MSM in Hanoi and Thai Nguyen

Abstract: Little is known about the effect of the social environment on HIV risk in gay men in northern Vietnam, particularly in rural areas. This qualitative research study conducted 4 key informant interviews and 30 in-depth interviews of men in two northern Vietnamese cities: Hanoi, a large city, and Thai Nguyen, a smaller town. Hanoi has experienced a growth in the number of places where gay men can socialize, access HIV prevention services, and discuss health issues. Thai Nguyen lacks these open venues. However, ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 17 publications
2
17
0
Order By: Relevance
“…Although Vietnamese in Chicago were living in a Western society and as a group had received more education, their higher levels of stigma on a range of issues might be related in part to their older age and the likelihood that they left Vietnam rooted in traditional values and perceptions. A recent study performed in Vietnam found that HIV infected injection drug users experienced support and concern from their families, even as they faced stigma and discrimination in their communities [16]. The findings regarding HIV suggest that Vietnamese living in Chicago also might express higher levels of HBV stigma than persons in Ho Chi Minh City due to a decrease in extended family connections and social support in the US.…”
Section: Discussionmentioning
confidence: 99%
“…Although Vietnamese in Chicago were living in a Western society and as a group had received more education, their higher levels of stigma on a range of issues might be related in part to their older age and the likelihood that they left Vietnam rooted in traditional values and perceptions. A recent study performed in Vietnam found that HIV infected injection drug users experienced support and concern from their families, even as they faced stigma and discrimination in their communities [16]. The findings regarding HIV suggest that Vietnamese living in Chicago also might express higher levels of HBV stigma than persons in Ho Chi Minh City due to a decrease in extended family connections and social support in the US.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to stigma related to sex work, homosexuality is stigmatized in Vietnam, although particularly in urban areas this may be decreasing (Colby and Cao 2004; Blanc 2005; Berry et al 2013). In this study, disclosure of sexual orientation to healthcare workers was significantly associated with increased sex-work related stigma.…”
Section: Discussionmentioning
confidence: 99%
“…Homosexuality remains highly stigmatized (Berry et al, 2013), and high HIV prevalence rates are seen among MSM, including male sex workers (Nguyen et al, 2008). …”
Section: Introductionmentioning
confidence: 99%